“Da árvore do conhecimento, não comereis o fruto”: o caráter neoconservador cristão da Escola sem Partido - Guidotti, Vitor Hugo Rinaldini (Universidade Federal de São Carlos, 2023)
The activist association "Escola sem Partido" (ESP) operated from 2004 to 2020, playing a significant role during the major rise of neoconservatism in Brazil. It stood out for its advocacy of agendas aimed at restricting critical perspectives in the field of education. The aim of this research was to address, from a sociological perspective, the Christian neoconservative influence on ESP, exploring the strategies and foundations it mobilized for its activities. To achieve this goal, primary and secondary sources were analyzed, including publications on its website and blog, as well as information from its social media profiles. To analyze the blog content, elements of Textual Discourse Analysis and Categorical Content Analysis were employed. In addition, other materials were studied, such as data from other blogs, social media, and websites with pronounced neoconservative content, public speeches by its founder and leader Miguel Nagib, and reliable official documents and journalistic material. The research results reveal the strong Christian neoconservative influence on ESP, which underpinned its principles and guided its initiatives in the political, educational, religious, and legal fields. It was also possible to observe the mobilization of ESP's agendas, especially during electoral periods, particularly in the 2018 elections. Through this study, gaps in research were identified and addressed, aiming to contribute to a greater sociological understanding of ESP in the context of the rise of the far-right and neoconservatism in Brazil.

La asociación movimentista Escola sem Partido (ESP) estuvo activa de 2004 a 2020, desempeñando un papel importante durante el gran auge del neoconservadurismo en Brasil. Se destacó por su defensa de agendas que apuntaban a restringir perspectivas críticas en el campo de la educación. El objetivo de esta investigación fue abordar, desde una perspectiva sociológica, la influencia neoconservadora cristiana en la ESP, explorando las estrategias y fundamentos que movilizó para sus acciones. Para ello se analizaron fuentes primarias y secundarias, incluidas publicaciones en su sitio web y blog, así como información de sus perfiles en redes sociales. Para analizar el contenido del blog, empleamos elementos de Análisis Textual Discursivo y Análisis de Contenido Categórico. Además, estudiamos otros materiales, como datos de otros blogs, redes sociales y sitios web con fuerte contenido neoconservador, discursos públicos de su fundador y líder Miguel Nagib y documentos oficiales y material periodístico confiable. Los resultados de la investigación revelan la fuerte influencia neoconservadora cristiana en la ESP, que fundó sus principios y guió sus iniciativas en los siguientes campos: político, educativo, religioso y jurídico. También fue posible percibir la movilización de las agendas de la ESP, especialmente durante los períodos electorales, especialmente en las elecciones de 2018. A través de este estudio, se identificaron y buscaron llenar vacíos de investigación, con el objetivo de contribuir a una mayor comprensión sociológica de la ESP, en el contexto del ascenso de la extrema derecha y el neoconservadurismo en Brasil.
"From the tree of knowledge, thou shalt not eat the fruit": the Christian Neoconservative Character of the Escola sem Partido
"Del árbol del conocimiento, no comeréis el fruto": el carácter neoconservador cristiano de la Escola sem Partido
Keywords: Neoconservadorismo; Extrema direita; Escola sem Partido; Sociologia política; Sociologia da religião; Neoconservatism; Extreme right; Political sociology; Sociology of religion; Neoconservadurismo; Extrema derecha; Sociología política; Sociología de la religión; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS